Pengaruh pH dan Suhu terhadap Produksi Antibiotika dari Isolat Bakteri Endofitik pada Tumbuhan Andalas (Morus macroura Miq.) - Riski Budi Yani; Anthoni Agustien; Feskaharny Alamsjah (Metamorfosa: Journal of Biological Sciences, 2019)
The study used survey method and the data were analysed descriptively. The selection of the bacteria which produce antibiotic had been with paper disk method and used Escherichia coli and Staphylococcus aureus as the sample bacteria. This result showed pH 7,0 was succesful optimum pH antibiotic produced for Bacillus sp.1 and Bacillus sp.2. and 370C was the optimum temperature to antibiotic produced from Bacillus sp.1 and Bacillus sp.2.